The local origins of business formation - Emin Murat Dinlersoz; Timothy Dunne; John C. Haltiwanger; Veronika Penciakova (Federal Reserve Bank of Atlanta, 2023)
What locations generate more business ideas, and where are ideas more likely to turn into businesses? Using comprehensive administrative data on business applications, we analyze the spatial disparity in the creation of business ideas and the formation of new employer startups from these ideas. Startups per capita exhibit enormous variation across granular units of geography. We decompose this variation into variation in ideas per capita and in their rate of transition to startups, and we find that both components matter. Observable local demographic, economic, financial, and business conditions account for a significant fraction of the variation in startups per capita-and more so for the variation in ideas per capita than in transition rate. Income, education, age, and foreignborn share are generally strong positive correlates of both idea generation and transition. Overall, the relationship of local conditions with ideas differs from that with transition rate in magnitude and, sometimes, in sign: certain conditions (notably, the African American share of the population) are positively associated with ideas but negatively with transition rates. We also find a close correspondence between the actual rank of locations in terms of startups per capita and the predicted rank based only on observable local conditions-a result useful for characterizing locations with high startup activity.
Keywords: L26; R12; R23; 330; entrepreneurship; firm entry; business formation; business dynamism; economic geography